PROSPECTS FOR THE DEVELOPMENT OF PUBLIC POLICY IN THE FIGHT AGAINST DRUG TRAFFICKING, THE DIRECTIONS FOR ITS IMPROVEMENT - Z. Shhagapsoev; A. Tutukov (Вестник университета)
The article tells about the current state of the drug situation in the Russian Federation. Illicit traffic in narcotic drugs and psychotropic substances in the realities of the Russian state in recent years has increased significantly, providing a very negative and, in some cases, and "fatal" impact on society as a whole and its individual components, in particular. The author attempts to set the main directions of the state policy in the sphere of combating drug trafficking. The problems of prevention of crimes related to illicit trafficking in narcotic drugs and psychotropic substances.